2018
DOI: 10.1016/j.tiv.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

In vitro toxicity and in silico docking analysis of two novel selective AH-receptor modulators

Abstract: The mediator of dioxin toxicity, aryl hydrocarbon receptor (AHR), has also important physiological functions. Selective AHR modulators (SAHRMs) share some effects of dioxins, except for their marked toxicity. We recently characterised toxicologically two novel SAHRMs, prodrugs IMA-08401 and IMA-07101 in rats, demonstrating that they are far less deleterious than the most toxic AHR-agonist, TCDD. Here, we analysed the in vitro toxicity and in silico AHR binding of the respective active, deacetylated metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“…Of note, Delaq itself cannot be administered in vivo because of its low solubility and short half-life, suggesting that Laq is metabolized into Delaq in the local microenvironment. 32 Using complete AHR-deficient mice, 2 independent groups determined that the suppression of EAE by Laq administration is AHR dependent, although AHRindependent mechanisms may also play a role. 43,44 Indeed, the induction of brain-derived natriuretic factor, a glial neuroprotective factor, is driven by Laq in an AHR-independent manner, suggesting that Laq engages additional pathways in glial cells in addition to AHR to promote the production of neuroprotective factors and regulators of excitotoxic neurotransmitters including glutamate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, Delaq itself cannot be administered in vivo because of its low solubility and short half-life, suggesting that Laq is metabolized into Delaq in the local microenvironment. 32 Using complete AHR-deficient mice, 2 independent groups determined that the suppression of EAE by Laq administration is AHR dependent, although AHRindependent mechanisms may also play a role. 43,44 Indeed, the induction of brain-derived natriuretic factor, a glial neuroprotective factor, is driven by Laq in an AHR-independent manner, suggesting that Laq engages additional pathways in glial cells in addition to AHR to promote the production of neuroprotective factors and regulators of excitotoxic neurotransmitters including glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic metabolism leads to the breakdown of Laq to its deethylated metabolite Delaq (de-ethylated Laq), a potent AHR agonist. 32 However, it is still unclear whether Laq or its metabolite Delaq activates AHR to limit CNS inflammation. To address this point, we treated primary murine astrocyte cultures with equimolar concentrations of Laq or Delaq.…”
Section: Laq Metabolite Delaq Activates Ahr-driven Protective Mechanisms In Eaementioning
confidence: 99%
“…Not only did the employment of PAS-B structures of the homologous HIF-2α protein in complex with ligands as templates for modeling greatly improve the quality of the modeled binding site, but the inclusion of a certain degree of receptor flexibility in docking calculations enabled us and other investigators to better describe the binding event 19,2426 . On the basis of these novel approaches, recent docking studies not only allowed prediction of the binding modes of several AhR ligands but also led to the discovery of novel AhR agonists and SAhRMs 25,2730 . Moreover they contributed to the study of the role of the AhR in different physiological processes 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…These concerns revolve around the similar structure and mechanism of action of these compounds to those of the most potent AHR-ligands—dioxins, and in particular, TCDD [42]. Our recent in vitro studies with the active derivative of C2 proved it to have virtually equal potency in inducing CYP1A1 activity to TCDD in a rat hepatoma cell line and exhibit similar modelled binding properties to the ligand binding region of the AHR [61]. However, despite these similarities, our in vivo studies in rats demonstrated that C2 elicits only a fraction of the biological impacts of TCDD, with one of them being Cyp1a1 gene induction.…”
Section: Discussionmentioning
confidence: 99%